P101 Inflammatory pleural effusions: differentiating the diagnosis. (12th November 2019) - Addala, D; Mercer, RM; Lu, Q; Shepherd, G; Varatharajah, R; Thayanandan, A; Hassan, M; Bedawi, E; Mccracken, D; Asciak, R; Rahman, N
Abstract : Introduction: Diagnosing pleural infection can be challenging in the clinical setting. Positive microbiology is the gold standard, but pleural fluid culture requires days to establish and can be negative in 40% of patients with pleural infection. Rapid biomarker testing showing low pH, low glucose and very high LDH in pleural fluid is used to diagnose pleural infection in the correct clinical setting. Objectives: To establish the diagnostic accuracy of low pH, low glucose and very high LDH in pleural fluid for pleural infection and establish the common alternative diagnoses leading to this biochemical pattern. Methods: A retrospective analysis of pleural effusion results from a UK tertiary centre over a three year period. Pleural fluid results with either pH<7.2, Glucose <2.2 mmol/L or LDH>1000 IU/L (total 173) were assessed to establish the frequency of non-infective final diagnoses and the relative specificity of each parameter calculated for the diagnosis of pleural infection. Results: Of effusions with either a low pH, low glucose or LDH>1000 (n=173), the most common causes were infective 51% (n=89), with the most frequent alternative diagnosis malignant pleural effusion (MPE) 31% (n=53). Of note 10% (n=19) had co-existing malignancy and infection. The most common causative MPEs were lung 51%, mesothelioma 32% and breast 16%. In all pleural effusions with a pH<7.2 (n=47), 13% were non infective diagnoses with 4% MPE. In all pleural effusions with glucose<2.2 (n=57), 53% were due to non-infective diagnoses, and 30% due to MPE. In the cohort with pleural fluid LDH>1000 (n=129), 47% were non infective in aetiology, 30% due to MPE. Table 1 illustrates further specific diagnoses within each cohort. Conclusions: Pleural effusions with a low pH, low glucose or very high LDH often have a non-infective cause. While it may be appropriate to commence antimicrobial treatment, our results suggest that malignancy should be actively investigated. Pleural fluid pH<7.2 was the most specific marker for pleural infection. Further work is required to establish whether biomarkers such as fluid c-reactive protein and procalcitonin provide added value in diagnosing pleural infection, especially in the cohort of patients with malignancy.